Mechanism and Rheological Properties of High-Modulus Asphalt - Xinquan Xu; Guilin Lu; Jun Yang; Xinhai Liu (Advances in Materials Science and Engineering)
High-modulus asphalt concrete (HMAC) is considered as an effective paving material for addressing the increasing heavy traffic and rutting problems. Therefore, one high-modulus agent was used in this study to prepare high-modulus asphalt binder with different dosages. The objective of this study is to investigate the performance and modification mechanism of high-modulus asphalt. The effects of high-modulus agent on the viscoelastic properties of asphalt with different dosages were quantified via rheological tests as compared to base binder and styrene-butadiene-styrene- (SBS-) modified asphalt. Moreover, the modification mechanism of the high-modulus agent was examined using fluorescence microscopy and infrared spectrum test. Based on rutting and dynamic modulus tests, the differences of road performances between high-modulus modified asphalt mixture and SBS-modified asphalt mixture were compared. The results demonstrate that the high-modulus agent improves the high-temperature performance and viscoelastic properties of the matrix asphalt. When the dosage increases to 6.67%, the modification effect is better than that of the SBS-modified asphalt. Furthermore, the results of the rutting test show that the high-modulus modified asphalt mixture has better resistance to deformation than the SBS-modified asphalt mixture. The dynamic modulus test further demonstrates that the high-modulus modified asphalt mixture exhibits superior performance in high-temperature range. Fluorescence microscopy shows that the high-modulus agent particles can swell in the asphalt to form polymer links that improve the viscoelastic properties of the asphalt. Based on the results of the infrared spectrum test, it can be concluded that a high-modulus agent changes the asphalt matrix via physical blending modification.